The United Nations Framework Convention on Climate Change Secretariat as an orchestrator in global climate policymaking. (March 2021) - Hickmann, Thomas; Widerberg, Oscar; Lederer, Markus; Pattberg, Philipp
Scholars have recently devoted increasing attention to the role and function of international bureaucracies in global policymaking. Some of them contend that international public officials have gained significant political influence in various policy fields. Compared to other international bureaucracies, the political leeway of the Secretariat of the United Nations Framework Convention on Climate Change has been considered rather limited. Due to the specific problem structure of the policy domain of climate change, national governments endowed this intergovernmental treaty secretariat with a relatively narrow mandate. However, this article argues that in the past few years, the United Nations Framework Convention on Climate Change Secretariat has gradually loosened its straitjacket and expanded its original spectrum of activity by engaging different sub-national and non-state actors into a policy dialogue using facilitative orchestration as a mode of governance. The present article explores the recent evolution of the United Nations Framework Convention on Climate Change Secretariat and investigates the way in which it initiates, guides, broadens and strengthens sub-national and non-state climate actions to achieve progress in the international climate negotiations. Points for practitioners: The Secretariat of the United Nations Framework Convention on Climate Change has lately adopted new roles and functions in global climate policymaking. While previously seen as a rather technocratic body that, first and foremost, serves national governments, the Climate Secretariat increasingly interacts with sub-national governments, civil society organizations and private companies to push the global response to climate change forward. We contend that the Climate Secretariat can contribute to global climate policymaking by coordinating and steering the initiatives of non-nation-state actors towards coherence and good practice.